Dual Place of Street Art – the City vs the Internet - Gralińska-Toborek, Agnieszka (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
Street art (or more broadly urban art), as the name suggests, has its own specific place, which is the street. However one would be mistaken to think that this type of art can only be seen there. Most street art lovers know the works of their favourite artists primarily through the Internet, not only because this kind of art is ephemeral or not easily accessible (for example, due to its dangerous or exotic locations), but because it is perhaps the best documented art that has been created in the world. For artists and lovers of street art, the Internet has become a common space to share photos. More often than not, the Internet also becomes the only place where artistic ideas exist. Paradoxically, such art, which was supposed to be the nearest to the viewer in the physical sense, has become the nearest in the virtual sense. One can, however, hope that neither consumers of art. nor artists will have to give up their direct experience of art that builds our polysensory sensitivity.